Answers

2015-05-29T17:55:11+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
In a triangle :  angle A =2 * angle C
         so angle B = 180 deg - 2 angle C - angle C
         B = 180 - 3 C

we know that
   Sin 2C = 2 Sin C Cos C
   Sin 3C = 3 Sin C - 4 Sin³ C  = Sin C [ 3 - 4 Sin² C ] = Sin C [ 2 Cos 2C + 1 ]

we know that:  a  / Sin A  = b / Sin B = c / Sin C
  =>  a / Sin 2C  =  b / Sin 3C  = c / Sin C
  =>  a = 2 c Cos C             -- (1)
 and  b = c {1 + 2 Cos 2C ]     --- (2)

Now find    a² - c² =  4 c² Cos² C - c²
                         = c² [ 4 Cos² C - 1 ]
                         = c² [ 2 Cos 2C + 1 ]
  substitute from (2),
   a² - c² =c² * b/c  = bc
  =>      a² = c (b+c)
proved.

1 5 1
Comment has been deleted
Comment has been deleted
Comment has been deleted
Comment has been deleted
what happened ? is the above proof and answer correct ?